Road Fatalities And Forensic Medicine (International Journal of Food and Nutritional Sciences, 2022)
In the event of a fatal traffic accident, the death is recorded as a "unusual death," an inquest is held, and, if required, a forensic autopsy is carried out to establish any causative link between the accident and the death, identify the at-fault vehicle, and ascertain the accident's cause. A forensic autopsy of a fatal traffic accident victim must establish the cause of death as well as the mechanism of damage. To complete this analytical assignment, the corpse, the vehicles involved, and the accident scene must be observed. The procedure of examining whether the individuals involved in the accident had any diseases that would compromise their driving performance or were under the influence of alcohol or drugs is also essential to determining the cause of death. Promoting collaborative research between forensic medicine, clinical medicine, automotive engineering, and road engineering will be crucial. It will also be critical to take action to lessen the impact of drunk pedestrians and pedestrians with dementia, as well as to ensure that drivers are properly screened for alcohol and illegal drug use.